Surrogates for the Sovereign - Butler, David. author. aut Link
IX, 365 p.
Keywords: A study of the office of the Constitutional Head of State in Westminster-style Commonwealth countries. In this book specialist writers look at each country separately, describing the variants in infrastructure and in local custom.